Inhaled foreign bodies in children: A global perspective on their epidemiological, clinical, and preventive aspects1. Issue 4 (20th November 2012) - Foltran, Francesca; Ballali, Simonetta; Rodriguez, Hugo; (Sebastian) van As, Arjan B.; Passali, Desiderio; Gulati, Achal; Gregori, Dario
Abstract Context While several articles describe clinical management of Foreign Bodies injuries in the upper air tract, little epidemiological evidence is available from injury databases. Objective This article aims to understand the burden of airway FB injuries in high‐, low‐, and middle‐income countries as emerging from scientific literature. Data Sources One thousand six hundred ninety‐nine published articles 1978–2008. Study Selection A free text search on PubMed database ((foreign bodies) or (foreign body)) and ((aspiration) or (airways) or (tracheobronchial) or (nasal) or (inhalation) or (obstruction) or (choking) or (inhaled) or (aspirations) or (nose) or (throat) or (asphyxiation)) and ((children) or (child)). Data Extraction Information on reported injuries according to country, time period, children sex and age, FB type, site of obstruction, symptoms, signs, diagnostic and therapeutic procedures, delay at the diagnosis, complications, number of deaths. Results Serious complications occur both in high‐income and low‐middle income countries in a considerable proportion of cases (10% and 20%, respectively). Similarly, death is not infrequent (5–7% of cases). Conclusions Few countries have good systematic data collection and there's a lack of sensibility in parents and clinicians in terms of acknowledge of the choking risk. On the contrary, international surveillance systems able to collect information in a standardized way need to be implemented. Pediatr Pulmonol. 2013; 48:344–351. © 2012 Wiley Periodicals, Inc.